2020
DOI: 10.1177/0361198120919760
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Analysis of Real-Time E-Scooter Trip Data in Washington, D.C.

Abstract: The proliferation of micromobility, evolving from station-based to dockless bikeshare programs, has dramatically accelerated since 2017 with an influx of investment from the private sector to a new product, dockless e-scooter share. As an alternative to pedal bikes, e-scooters have become widespread across the U.S.A. owing to the unprecedented convenience they bring to commuters and travelers with electric-power propulsion and freedom from docking stations. In cities like Washington, D.C., e-scooter share can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(59 citation statements)
references
References 19 publications
6
53
0
Order By: Relevance
“…Nonetheless, this terminological ambiguity generated confusion in both academic and non-academic literature. For instance, Degele and colleagues [33] wrote about potential users of shared moped e-scooters in Germany and were cited in a couple of academic papers focused on standing e-scooters [34,35]. Similarly, a paper on injuries associated with e-bikes and moped scooters [36] was cited in an article focusing on the impact of standing e-scooters on pedestrian safety [37].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, this terminological ambiguity generated confusion in both academic and non-academic literature. For instance, Degele and colleagues [33] wrote about potential users of shared moped e-scooters in Germany and were cited in a couple of academic papers focused on standing e-scooters [34,35]. Similarly, a paper on injuries associated with e-bikes and moped scooters [36] was cited in an article focusing on the impact of standing e-scooters on pedestrian safety [37].…”
Section: Methodsmentioning
confidence: 99%
“…From a temporal perspective, emerging evidence suggests that shared e-scooters are more intensely used in the afternoon rather than the morning [35,42,43]. Moreover, some studies in North America show that average daily usage is higher on weekends and on special days such as public holidays [35,42,44,45].…”
Section: Usage Patternsmentioning
confidence: 99%
“…James et al [18] found that footpaths blocked by e-scooters are perceived as such by e-scooter riders significantly less often than by other road users (21% of e-scooter users vs. 75% of non-users). Especially in streets with high usage pressure, designated parking zones (ground markings, appropriate stands, or geo-fencing) for e-scooters can reduce these conflicts [33]. In addition, regulation of e-scooter parking, especially around PT stations, is considered to play a key role in strengthening intermodal mobility behavior [34].…”
Section: Literature Reviewmentioning
confidence: 99%
“…E-scooter share trip trajectories are provided at the street link level with a precise construction of the trajectory trip inventories [ 40 ]. The contribution of character individuals to the reduction of the heat alert through the bike-sharing system has been analysed in research, where the factors of age and gender show different behaviours.…”
Section: Literature Reviewmentioning
confidence: 99%